The Influence of Emotion in the Management of Amateur Football Organizations - Hebles, Melany; Prado-Gascó, Vicente Javier; Llanos-Contreras, Orlando; Alguacil, Mario (Frontiers in Psychology, 2020)
This article is oriented to the analysis of organisational and emotional variables in amateur sporting organizations. The general objective is to analyse the influence of organisational variables such as service quality, transactional leadership, and transformational leadership and emotional variables such as affective commitment, emotional attachment investment and emotional attachment dividend to predict the credibility that members of amateur sporting organisations perceive, as well as their degree of identification and loyalty. The opinions of 203 members of Chilean amateur football teams, (169 men and 34 women, with ages between 18 and 68 years (Mean=32.75 years, DT= 9.92) have been analysed through a self-completed questionnaire. To reach the objectives, two types of differential but complementary analyses, in the form of hierarchical regression models (from hereon in HRM) and qualitative comparative analysis (from hereon in QCA), were performed. The results obtained suggest that the organisational variables are better predictors than the emotional variables in all of the cases and in the same way the inclusion of the emotional variables improves the predictive capacity of the proposed models to explain identification and loyalty, but not in the case of credibility. In general, the variables considered seem to explain 37% of the credibility, 56% of loyalty and 65% of identification. On the other hand, considering the results of the QCA, no variable turned out to be necessary, but different combinations of variables (conditions) were observed that were able to explain between 47and 91% of the cases of the variables analysed. In general, based on these results, it was observed that the emotional variables were important in interaction with other organizational ones, due to the fact that they are present in the three combinations that most explain identification and loyalty, and are also present in the three combinations that most explain credibility. This study contributes to the literature by supporting the importance of managing emotions in order for sporting organizations to be more successful.